Systematic Literature Review : The Role Of Financial Reports In Improving Government Accountability And Transparency - Selia Meilantika; Enggar Diah Puspa Arum (Cita konsultindo, 2025)
This study aims to identify and analyze the role of financial reports in realizing transparency and accountability in local governments through a Systematic Literature Review (SLR) approach. The main focus of this study is to map trends, themes, methods, and research gaps related to accountability and transparency in public sector financial reporting in Indonesia. This study is a Systematic Literature Review (SLR) of 20 scientific articles selected from a total of 1,310 articles obtained through the SINTA-accredited national journal database and several internationally indexed sources. The analysis was conducted descriptively by examining the thematic focus, research methods, and empirical relevance between financial reports, transparency, and public accountability in the 2016-2025 period. The results of the study indicate that financial reports play a significant role in improving government accountability and transparency. Analysis of research from 2016-2025 revealed that the quality of report presentation, information accessibility, and the implementation of electronic financial systems such as e-budgeting and SIPD consistently strengthen transparency, efficiency, and public trust. However, challenges remain, including limited human resources, system integration, and public literacy. Overall, financial reports serve a strategic function as an instrument for establishing transparent and accountable governance. The findings of this study emphasize the importance of financial reports as a strategic tool in strengthening public trust and accountability in local governments. The results can serve as a reference for local governments in strengthening financial reporting systems, digitizing fiscal information, and increasing the capacity of public finance officials. This study provides novelty in the form of a systematic mapping of research trends, directions, and gaps regarding the relationship between financial reports, transparency, and public sector accountability in Indonesia, and offers directions for further research related to the digitalization and transformation of financial reporting.